ADAPTASI PENGHUNI DARI PERMUKIMAN KUMUH KE HUNIAN BERKONSEP RISHA STUDI KASUS: RUSUNAWA SUBKOMUNAL RISHA SEMANGGI DI SURAKARTA - Audrey Mellinda Christy, Karel; Budiyuwono, Hartanto (Jurnal Riset Arsitektur, 2024)
Abstract - Syarif Burhanuddin, the Director of PUPR, has urged to individuals living in uninhabitable houses in slum areas to move to government-provided flats as soon as possible. Aside from being a nice place to live, the low cost apartment's construction aims to limit the use of residential land in urban areas. The migration of people from slums to low cost apartment will result in new ideas, difficulties, and changes in the condition and way of life of low-income people. The development of the Sub Communal Low-Cost Apartment in Semanggi region, based on the concept of a simple healthy immediate house (RISHA), is one strategy to eliminate slum settlements in Surakarta City. The RISHA Sub Communal Low-Cost Apartment's construction innovation is based on the necessity to speed up the provision of housing at a price that low-income people can afford, while keeping the building's quality and meeting the requirements for livable housing. By documenting the current situation of the RISHA Subcommunal Low-Cost Apartment and comparing it to the conditions of slum settlements in the Semanggi Area before 2018, the study utilized a descriptive method with a qualitative approach. Field observations, interviews, and literature studies were used to gather data on the Semanggi RISHA Sub-communal Low Cost Apartment. The goal of this research is to figure out how the physical and social adaptation of residents that lived in slums in the Semanggi Area before moving to the RISHA Sub-communal Low Cost Apartment. The study employs data analysis approaches such as data reduction, data presentation, and conclusion drafting. The findings of this study show that communities affected by relocation adjust their lifestyle in order to adapt to new environmental conditions as a result of the organization of slum settlements in Mojo Village. Physical and social adaptations take place in the residents of the RISHA Sub-communal Low Cost Apartment. Keywords: RISHA, slum settlement, relocation, adaptation, Semanggi.